162 Regulated Exosome Secretion by Vascular Smooth Muscle Cells Mediates Vascular Calcification. (31st May 2014) - Kapustin, Alexander; Chatrou, Martijn; Kalra, Sundeep; Drozdov, Ignat; Soong, Daniel; Furmanik, Malgorzata; Alvarez-Hernandez, Daniel; Shroff, Rukshana; Yin, Xiaoke; Muller, Karin; Skepper, Jeremy; Mayr, Manuel; et al.
Abstract : Arterial stiffening caused by deposition of calcium phosphate salts in the vessel wall is common in patients with atherosclerosis, renal failure and diabetes and contributes to high cardiovascular morbidity and mortality in these groups. Medial calcification is mediated by vascular smooth muscle cells (VSMCs) which undergo phenotypic transitions and secrete matrix vesicles (MVs) that form the first nidus for mineralization. In this study we studied the mechanisms regulating MV secretion and compared them with circulating calcifying calciprotein complexes and exosomes. Phenotypic modulation of human aortic VSMCs was induced by TGF-β1 or PDGF-BB. MVs and extracellular vesicles were isolated from cell media or platelet-free plasma, by differential ultracentrifugation and compared using Nanosight LM-10, flow cytometry, immunogold labelling, transmission electron microscopy and western blotting. We found that MVs are secreted from multivesicular bodies and enriched with the exosomal markers, CD63, CD81, CD9 and MHC I. Exosome secretion was regulated by the exosome biogenesis regulator, sphingomyelin phosphodiesterase 3 (SMPD3), and inhibition of SMPD3 prevented VSMC calcification. Treatment of VSMCs in calcifying conditions and loss of the contractile phenotype were both associated with elevated exosome secretion and increased calcification. In agreement with our in vitro data, MVB-like structures were observed in VSMCs ex vivo as shown by EM analysis of human vessel rings. Immunohistochemical staining revealed that the exosome markers, CD63 and annexin A6 were present in the extracellular (ECM) at sites of vascular calcification in vivo . Importantly, only exosomes secreted by VSMCs in calcifying conditions contained amorphous calcium phosphate crystals as detected by EDX analysis. Nanosite analysis revealed that calcifying VSMC-derived exosomes are similar in size to non-calcifying exosomes (mode 136 +/- 3.6 nm and 147+/- 5.9 nm, correspondingly) and were similar to exosomes, isolated from the blood (Mode 146+/-14 nm). Calcifying exosomes were also distinct from calcium phosphate crystals (mode 107 +/- 7 nm) and fetuin-A containing calciprotein particles (mode 182 +/- 9.3 nm). Our data indicate that vascular calcification is mediated by VSMC-derived exosomes and that loss of the contractile VSMC phenotype and mineral imbalance promote calcification by enhanced exosome secretion. Calcifying exosomes are distinct from calcium phosphate crystals or calciprotein particles, and may be presented in the circulation where their levels may be a novel indicator of vascular calcification.